P04.02 Postponing the medical treatment is possible in selected cases of diffuse low-grade glioma with foci of WHO grade III-IV after total or subtotal resection. (6th September 2019) - Darlix, A; Rigau, V; Fraisse, J; Gozé, C; Fabbro, M; Duffau, H
Abstract: BACKGROUND: Diffuse low-grade gliomas (DLGG) are defined by a continuous growth and an unavoidable malignant transformation. Foci of malignant transformation may be found within DLGG samples obtained from surgical resections. As the medical management is classically based on the higher tumor grade, an immediate adjuvant treatment is usually proposed (radiotherapy [RT] with Temozolomide or PCV), whatever the extent of resection. Yet, early RT has no impact on overall survival compared with late RT, and is associated with cognitive toxicity. An alternative approach consists in postponing the medical treatment in selected patients. MATERIAL AND METHODS: We conducted a monocentric retrospective analysis of a consecutive series of patients managed with this conservative approach. Inclusion criteria were: DLGG (WHO 2016 grade II) with at least one focus of malignant transformation (grade III-IV); no previous chemotherapy or RT; no less than a subtotal resection of the FLAIR tumor volume; no intention of treating with immediate adjuvant therapy; at least two years of postoperative follow-up. The time interval to the next medical treatment (chemotherapy and/or radiotherapy) was assessed, as well as the functional and survival results. RESULTS: Forty-five DLGG patients, of median age 36.5 years, were included in the analysis (median time interval from diagnosis: 7.3 months). The histo-molecular diagnosis was diffuse astrocytoma, IDH mutant in 46.7% of cases, astrocytoma, IDH wild-type in 13.3% and oligodendroglioma, IDH mutant and 1p/19q codeleted in 40.0%. Ten tumors presented with grade IV foci. The quality of resection was subtotal (FLAIR tumor residue ≤15 cm 3 ) in 73.3%, total (no FLAIR tumor residue) in 24.4% and supratotal in 2.2%. After surgery, patients were managed with regular clinical and radiological follow-up. With a median postoperative follow-up of 6.3 years, 75.5% of patients received a subsequent medical treatment, after a median time interval of 3.7 years. The first treatment after surgery consisted of repeated surgery in 11 patients, Temozolomide in 28 patients, RT in one patient. At the time of analysis, 19 patients (42.2%) had been treated with RT, after a median time interval of 9.5 years. Nine patients (20.0%) had died (median overall survival not reached, 5-years and 7-years survival rates: 95.2% and 67.0%). Most surviving patients were still active professionally (69.4%), with a median Karnofsky performance status of 90, and no or rare seizures. CONCLUSION: In this series, total or subtotal resection of DLGG with a least one focus of grade III-IV glioma radically changed the natural history of these tumors and allowed delaying the following medical treatment by several years. This strategy is feasible in selected patients and should be considered on a case-by-case basis in patients with foci of malignant transformation following total or subtotal resection.